2015
DOI: 10.33584/jnzg.2015.77.461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of closing date on seeding and hardseededness of balansa, gland, Persian and arrowleaf clovers on East Coast dryland

Abstract: Four annual clovers (Arrowleaf (Trifolium versiculosum), balansa (T. michelianum), Persian (T. resupinatum) and gland (T. glanduliferum)) were sown on five East Coast dryland farms and one moist Taranaki site. Hardseededness was measured at all sites and seed production and hardseededness was measured at three sites following different closing dates. There were no differences in seed size for any species between sites or closing dates. High levels of seed (500-700 kg/ha) were set by balansa and arrowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…It research work, in a similar manner to lucerne. Sub clover Pennell (2000), Smetham (2003) and latterly Lucas et al (2015) and MacFarlane et al (2015), as an appropriate legume for summer dry, drought-prone regions totalling about 3-4 million ha of New Zealand. Sub clover is one of the earliest spring producing legumes and its growth pattern matches the feed demand of lactating ewes and can be used to complement lucerne in a farm systems (Brown et al 2006).…”
Section: Subterranean Clover (Trifolium Subterraneum)mentioning
confidence: 99%
See 3 more Smart Citations
“…It research work, in a similar manner to lucerne. Sub clover Pennell (2000), Smetham (2003) and latterly Lucas et al (2015) and MacFarlane et al (2015), as an appropriate legume for summer dry, drought-prone regions totalling about 3-4 million ha of New Zealand. Sub clover is one of the earliest spring producing legumes and its growth pattern matches the feed demand of lactating ewes and can be used to complement lucerne in a farm systems (Brown et al 2006).…”
Section: Subterranean Clover (Trifolium Subterraneum)mentioning
confidence: 99%
“…However, the production of sub clover seed is an invasive process that raises environmental concerns when buried seed is excavated, and there are no specialist seed harvesters in New Zealand. Whether sub clover seed can be commercially produced in New In addition, many of the cultivars imported have an extremely high hardseed level and as a result have not been evaluated for their performance in New Zealand pasture systems (Lucas et al 2015;MacFarlane et al 2015) restricting the potential of this species.…”
Section: Subterranean Clover (Trifolium Subterraneum)mentioning
confidence: 99%
See 2 more Smart Citations
“…Arrowleaf clover is an erect, aerially seeding species which is hard seeded and has the potential in New Zealand to produce significantly more spring dry matter than either white (T. repens) or subterranean (T. subterraneum) clovers (Evans & Mills 2008). An initial study, on dryland hill country sown with a mix of plantain (Plantain lanceolata) and other clovers, showed that an early closing date (fenced off from grazing) resulted in seed yields of 500-700 kg/ha (MacFarlane et al 2015). This work was extended to two other dryland hill sites where arrowleaf clover was established as a sole crop with the objective of maximising seed set.…”
Section: Introductionmentioning
confidence: 99%